Self-Initiated Expatriates : the case of International students - Couloigner, Suzanne (2016)
The expatriation of workers is in itself not a new topic. However, literature on self-initiated expatriates (SIE) have been overlooked and is still quite scarce. At the same time, students going abroad to follow an overseas education is increasing. Therefore, this dissertation aims at understanding what the motives to work abroad are for a SIE with an international education and how those differ from the motives of 'standard' SIE, a priori without an overseas education. Based on a qualitative approach, this dissertation highlights that SIE with an international education are motivated for a career as SIE by job opportunities, financial situation and the influence of the 'right timing', with barely consideration for travelling or discovering a new culture. Two other major themes were revealed from the findings, namely the role that an international education had on the respondents and the influence of Brexit. Brexit emerged as an unexpected theme, due its very recent birth, and this dissertation could only hope be the starting point for future studies.